From Supporting Role to Leading Role: China’s Voice at Two Centennial Conferences - ZHAO, Bifang (Journal of Research for Christianity in China (JRCC), 2025)
By 1907, the centenary of Protestantism’s arrival in China, the balance of power between China and the West had begun to shift noticeably. Missionaries convened the Centennial Missionary Conference in Shanghai, serving both to commemorate a century of missionary achievements and to deliberate on future missionary endeavors in China. Missionaries invited Chinese government representatives and senior Chinese Christians to participate in various commemorative events. The Chinese side seized this opportunity to articulate their own positions and perspectives, projecting an image of harmonious Sino-Western relations. However, the absence of Chinese representatives with voting rights at the Shanghai Centennial Conference sparked discontent and skepticism among Chinese Christians. In Guangdong, where the church enjoyed greater autonomy, a group of Christian leaders deeply rooted in national sentiment and patriotic fervor decided to organize a separate commemorative assembly for Chinese Christians at their own expense. Local officials provided strong support for this initiative. Between the two conferences, Chinese Christians achieved a transformation from supporting roles to protagonists. Through their actions, they demonstrated their capabilities and a strong sense of independence in managing church affairs, providing an early exploration for the formation of a new Protestant power structure in China.